Efikasi Diri Multikultur dan Hubungannya dengan Konsep Diri Akademik Siswa Sekolah Menengah Atas - Pristianingsih, Vianda; Yosef, Yosef (Jurnal Bimbingan dan Konseling Terapan, 2021)
ABSTRACTThis study aimed to investigate the relationship between the two at the high school level using a correlational research design. Two instruments, namely the Multicultural Self-Efficacy Scale and the Academic Self-Concept Scale, were administered to 302 high school students randomly selected as respondents. The study employed Pearson's product-moment correlation to analyze the relationship between the two variables using SPSS 25 for Windows Release. This study also displayed descriptive data from each variable according to gender and grade level. The results found a positive relationship at a moderate level between students' multicultural self-efficacy and students' academic self-concept (r=0.488). In addition, 70.9% of students had a multicultural self-efficacy level in the medium to the very high category, and 81.5% had medium to very high levels of academic self-concept. Meanwhile, based on grade level, the data of the two variables showed the same position, that the tenth graders had the highest score (7.99 and 3.53), followed by the eleventh graders (7.77 and 3.50), and the twelfth graders (7 .49 and 3.45).Keywords: multicultural self-efficacy, academic self-concept, high school student  ABSTRAKPenelitian ini dimaksudkan untuk menyelidiki hubungan keduanya di tingkat sekolah menengah atas dengan menggunakan desain korelasional. Dua instrumen, yaitu Skala Efikasi Diri Multikultur dan Skala Konsep Diri Akademik, diadministrasikan kepada 302 siswa SMA yang dipilih secara acak sebagai sampel. Korelasi product moment dari Pearson digunakan untuk menganalisis hubungan kedua variabel dengan memanfaatkan SPSS 25 for Windows Release. Penelitian ini juga menampilkan data deskriptif dari masing-masing variabel menurut jenis kelamin dan tingkat kelas. Hasil riset menemukan adanya hubungan positif pada level moderat antara efikasi diri multikultural siswa dan konsep diri akademik siswa (r=0,488). Kemudian, 70,9% siswa memiliki tingkat efikasi diri multikultural pada kategori antara sedang-sangat tinggi dan 81,5% siswa memiliki konsep diri akademik kategori sedang-sangat tinggi. Sementara itu berdasarkan tingkatan kelas, data kedua variabel menunjukkan kesamaan posisi, yaitu siswa kelas X memilih skor tertinggi (7,99 dan 3,53) , diikuti oleh siswa kelas XII (7,77 dan 3,50), dan kelas XI (7,49 dan 3,45).Kata kunci: Efikasi diri multikultural, Konsep diri akademik, siswa sekolah menengah atas